Synthesis and characterization of electroactive gellan gum spongy-like hydrogels for skeletal muscle tissue engineering applications - Berti, F. V. (2017)
Advances on materials' research for tissue engineering (TE) applications have shown that animal cells respond directly to the material physical, chemical, mechanical, and electrical stimuli altering a variety of cell signaling cascades, which consequently result in phenotypic and genotypic alterations. Gellan gum (GG) spongy-like hydrogels (SLH) with open microstructure, mechanical properties, and cell performance have shown promising results for soft TE applications. Taking advantage of intrinsic properties of GG-SLH and polypyrrole (PPy) electroactivity, we developed electroactive PPy-GG-SLH envisaging their potential use for skeletal muscle TE. Three different methods of in situ chemical oxidative polymerization were developed based on the availability of pyrrole: freely dissolved in solution (method I and III) or immobilized into GG hydrogels (method II). PPy was homogeneously distributed within (method I and III) and on the surface (method II) of GG-SLH, as also confirmed by Fourier Transform infrared spectra. PPy-GG-SLH showed higher conductivity than GG-SLH (pâ <â 0.05) whereas PPy-GG-SLH (method I and II) showed the best conductivity among the 3 methods (â ¼1 to 2â Ã â 10-4Â S/cm). The microarchitecture of PPy-GG-SLH (method I) was similar to GG-SLH but PPy-GG-SLH (method II and III) presented smaller pore sizes and lower porosity. PPy-GG-SLH (method I and II) compressive modulus (â ¼450-500 KPa) and recovering capacity (â ¼75-90%) was higher than GG-SLH, nevertheless the mechanical properties of PPy-GG-SLH (method III) were lower. The water uptake of PPy-GG-SLH was rapidly up to 2500% and were stable along 60 days of degradation being the maximum weight loss 20%. Mechanically stable and electroactive PPy-GG-SLH (method I and II) were analyzed regarding cellular performance. PPy-GG-SLH were not cytotoxic for L929 cells. In addition, L929 and C2C12 myoblast cells were able to adhere and spread within PPy-GG-SLH, showing improved spreading in comparison to GG-SLH performance. Overall, PPy-GG-SLH show promising features as an alternative electroactive platform to analyze the influence of electrical stimulation on skeletal muscle cells.